PENGARUH METODE PEMBELAJARAN BERBASIS MASALAH (PBL) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP TASAWUF MAHASISWA PAI UNIVERSITAS SUNAN GIRI SURABAYA: Pengaruh Problem-Based Learning Terhadap Pemahaman Konsep Tasawuf Pada Mahasiswa PAI - Robbani, Hamdan; Ghozali, Solchan (Transformation of Islamic Management and Education, 2025)
This study aims to analyze the effect of the Problem-Based Learning (PBL) method on the ability to understand the concept of Sufism of students at the Islamic Religious Education Study Program, Sunan Giri University, Surabaya. The background of this study is based on the problem that abstract and philosophical Sufism learning is often difficult for students to understand if it is only taught through conventional lecture methods. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group pretest-posttest design. The research sample consisted of 60 students who were divided into an experimental group with PBL learning and a control group with conventional learning. Data collection instruments were in the form of a Sufism concept understanding test, observation sheets, and student response questionnaires. The results of the analysis showed that the application of PBL significantly increased the average score of understanding the concept of Sufism compared to conventional methods with a calculated F value of 28.74 and an effect size of 0.67. Observation and questionnaire data also support that PBL encourages active participation and helps students relate the concept of Sufism to contemporary spiritual problems. The implications of this study indicate that PBL can be an alternative effective learning method to ground Sufism teachings in Islamic higher education environments. In addition to being relevant in Indonesia, the PBL model has the potential to be adapted in various international and cross-cultural contexts to support more contextual, reflective, and applicable spiritual learning.